The integration of mind mapping strategy on students’ essay writing at universities kristen Indonesia - Lamhot Naibaho (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study investigates the integration of mind mapping strategy on students' essay writing at Universities Kristen Indonesia, and it was done at Universitas Kristen Indonesia. The study method used was a quantitative method with a quasi-experimental design. The population was the third-semester students and the fifth-semester students, which consisted of two classes. Both classes consist of 43 students. The instrument of this research is a writing test. The test was administered as a pre-test and post-test to the experimental and control group. Data were collected and analysed using SPSS version 18. T-tests at the 0.5 level and covariance analysis are used to analyse the data. The result is that mind maps are one of the learning alternatives that teachers can use in teaching essay lessons. Students' performance in the experimental group increased compared to students in the control group by using mind maps, and the mind map is an important teaching material for the students. Then it is suggested that the mind mapping could be used by lecturers as an alternative to improve the students' ability in writing the essay.